A pilot study : can mindfulness help high performance athletes? : a Masters thesis presented in partial fulfilment of the requirements for the degree of Masters of Science in Psychology, Massey University, Wellington, New Zealand - Rapley, Taylor (Massey University, 2021)
To investigate whether mindfulness is effective for decreasing perceived stress in high performance athletes experiencing high levels of stress, the current single case pilot study (SCD) employed a Mindfulness Based Intervention (MBI) consisting of a video recorded mindfulness psychoeducation session, followed by the ‘1 Giant Mind – Learn to Meditate’ phone application. Participants (N = 3) were instructed to use the ‘1 Giant Mind – Learn to Meditate’ smartphone application and meditate once a day for 30 days. The study measured participants' perceived stress, psychological inflexibility, dispositional mindfulness and self-compassion at baseline, mid and post intervention. Mindfulness psychoeducation and meditation effectively decreased perceived stress and psychological inflexibility, and increased dispositional mindfulness and self-compassion from baseline to post intervention for all three participants, with a large group level effect across all four measures. Given that athletes are particularly vulnerable to experiencing the detriments of stress, this research is necessary to gain a better understanding of the benefits of mindfulness psychoeducation and meditation on high performance athletes experiencing high levels of stress.
Keywords: 520406 Sensory processes, perception and performance